2014
DOI: 10.1002/ange.201401024
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(0)‐ und Platin(0)‐Bis‐NHC‐Chelatkomplexe

Abstract: d 10 -ML 2 -Fragmente sind seit langem für ihr Potenzial bekannt, unreaktive Bindungen durch oxidative Addition zu aktivieren. Bei der Entwicklung aktiverer Spezies haben sich zwei Ansätze bewährt: Der Einsatz von starken s-Donorliganden, die zu elektronenreichen Metallzentren führen, sowie von Chelatliganden, die eine gewinkelte Koordinationsgeometrie erzeugen. Wir haben beide Strategien kombiniert und Nickel(0)-sowie erstmals Platin(0)-Bis-NHC-Chelatkomplexe synthetisiert. Bis(1,5-Cyclooctadien)nickel(0) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…90 The complexes have been used to synthesize Ni(0) and Pt(0) complexes with chelating bis(NHC) ligands. 91 Westerhausen et al reported that addition of the free methylene bridged bis (NHC) to LiHMDS leads to the chelating bis(NHC) adduct 17. 92 Crystal structure analysis shows a monomeric structure with both NHC moieties connected to the lithium center (d (Li−C) = 2.271(4) and 2.234(4) Å), which is also coordinated by one [N(SiMe 3 ) 2 ] ligand.…”
Section: Nhc Complexes Of Group 1 Metalsmentioning
confidence: 99%
“…90 The complexes have been used to synthesize Ni(0) and Pt(0) complexes with chelating bis(NHC) ligands. 91 Westerhausen et al reported that addition of the free methylene bridged bis (NHC) to LiHMDS leads to the chelating bis(NHC) adduct 17. 92 Crystal structure analysis shows a monomeric structure with both NHC moieties connected to the lithium center (d (Li−C) = 2.271(4) and 2.234(4) Å), which is also coordinated by one [N(SiMe 3 ) 2 ] ligand.…”
Section: Nhc Complexes Of Group 1 Metalsmentioning
confidence: 99%